Clinical Feature, Treatment, and KCNH5 Mutations in Epilepsy - Hu, Xiufu; Yang, Junli; Zhang, Man; Fang, Tie; Gao, Qin; Liu, Xinjie (Frontiers in Pediatrics, 2022)
The voltage-gated Kv10.2 potassium channel，encoded by KCNH5，is expressed broadly in mammalian tissues including the brain. Its potential mechanism still remains not fully clear. In accordance with previous studies, the dysfunction of Kv10.2 may be associated with epileptic encephalopathies and autism spectrum disorder (ASD). To date, only 1 disease-causing mutation of KCNH5 have been reported. The case presented with seizures and autism symptoms. In the present study，we report the discovery and characterization of 3 de novo mutations in KCNH5 which can be the cause of the severe conditions observed in these patients in 3 Chinese children. All of them experienced seizure, two of them present with epileptic encephalopathy, one of them presents with ASD, one does not relapse after the drug withdrawal. Notably, treatment of antiepileptic drugs (AEDs) was effective in all patients that their epileptic seizures were controlled. The structures of the proteins resulting from the mutations were predicted in two of the three cases. This provides a powerful insight into clinical heterogeneity and genotype-phenotype correlation in KCNH5 related diseases.